STUDI PENGELOLAAN SAMPAH TERPADU DI BANK SAMPAH BERSERI KOTA KEDIRI - Widuri, Laily Ilman; Agustin, Vira Audita; Khozin, Mohammad Nur; Siswoyo, Tri Agus (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2025)
Waste management in urban areas is a serious issue if it is not handled properly and with special attention to management activities. Properly managed waste can provide economic value if it is sorted and processed at the source. The Waste Bank “BERSERI” in Burengan Village, Kediri City, plays an important role in reducing the amount of waste in urban areas through a participatory approach to the community. This community service activity aimed to provide an overview of waste management activities at the Waste Bank and to outline the involvement of the community and relevant parties in supporting waste management activities at the Waste Bank “BERSERI” in Kediri City. The community service activities conducted by the Service Team included discussions and interviews during a visit to the BERSERI Waste Bank location. The results of the interviews indicated that the Waste Bank “BERSERI” has collected various types of inorganic waste through mechanisms including sorting, weighing, recording, and distributing the proceeds from waste sales to customers. The waste collected has also been recycled into valuable products, both from inorganic and organic waste. The existence of waste bank management heavily depends on active community participation and the roles of various parties, including the government, universities, and the private sector.